Modelamento estocástico da dinâmica do livro de ordens: uma aplicação ao mercado brasileiro - Tomazella, Luiz Henrique Bincoletto (2015)
This paper deals with the importance of modeling the dynamics of book orders for the understanding of this market microstructure. Therefore, applying the modeling techniques of the order book using the stochastic model proposed by Cont, Stoikov e Talreja (2010) the Brazilian stock market. Once applied the model we analyze the results obtained from the perspective of other empirical studies, such as Bouchaud et al. (2002). After the estimation and analysis of the results were performed simulations to see if the parameters found reflect the dynamics of the local market, for different scenarios standardization of the size of orders. Finally, with the analysis of the results, it was concluded, with some reservations, that the proposed model is valid for the Brazilian stock market, as shows the impact of the liquidity of assets in comparison to the parameters found in other international markets .